2011
DOI: 10.1007/s00248-011-9955-z
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Diversity Associated to the Olive Moth, Prays Oleae Bernard: A Survey for Potential Entomopathogenic Fungi

Abstract: Olive production is one of the main agricultural activities in Portugal. In the region of Trás-os-Montes, this crop has been considerably affected by Prays oleae. In order to evaluate the diversity of fungi on Prays oleae population of Trás-os-Montes olive orchards, larvae and pupae of the three annual generations (phyllophagous, antophagous and carpophagous) were collected and evaluated for fungal growth on their surface. From the 3,828 larvae and pupae, a high percentage of individuals exhibited growth of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 37 publications
3
36
1
2
Order By: Relevance
“…Different studies suggest that Metarhizium spp. are either absent (Ali-Shtayeh et al 2003, Oliveira et al 2012 or less prevalent in the Mediterranean region (Tarasco et al 1997, Asensio et al 2003, Quesada-Moraga et al 2007, Garrido-Jurado et al 2015. Surprisingly, Garrido-Jurado et al (2015) reported just four isolates of M. robertsii from 270 soil samples in Spain which was quite a small number compared with the 11 isolates from 183 soil samples found in the present study.…”
Section: Fungal Abundance and Diversitycontrasting
confidence: 73%
“…Different studies suggest that Metarhizium spp. are either absent (Ali-Shtayeh et al 2003, Oliveira et al 2012 or less prevalent in the Mediterranean region (Tarasco et al 1997, Asensio et al 2003, Quesada-Moraga et al 2007, Garrido-Jurado et al 2015. Surprisingly, Garrido-Jurado et al (2015) reported just four isolates of M. robertsii from 270 soil samples in Spain which was quite a small number compared with the 11 isolates from 183 soil samples found in the present study.…”
Section: Fungal Abundance and Diversitycontrasting
confidence: 73%
“…Total genomic DNA was extracted from mycelial/spores using the REDExtract-N-Amp™ Plant PCR kit (Sigma, Poole, UK). The ITS region (ITS1, 5.8S, ITS2) was amplified using the universal ITS1 and ITS4 primers in a PCR protocol formerly described by Oliveira et al (2012). The amplified products (∼650 bp) were purified and sequenced using Macrogen Inc. (Seoul, South Korea) services, using the same primers to initiate the reaction.…”
Section: Identification Of Fungal Isolatesmentioning
confidence: 99%
“…The ITS region (ITS1, 5.8S, ITS2) was amplified using the universal ITS1 and ITS4 primers (White et al 1990) and the PCR protocol described by Oliveira et al (2012). Amplified products (*600 pb) were purified using JETQUICK PCR Product Purification Spin Kit (Genomed) following the manufactureŕs instructions.…”
Section: Identification Of Fungal Isolatesmentioning
confidence: 99%
“…Genomic DNA was extract from spores or mycelial mat following the protocol of Oliveira et al (2012). The ITS region (ITS1, 5.8S, ITS2) was amplified using the universal ITS1 and ITS4 primers (White et al 1990) and the PCR protocol described by Oliveira et al (2012).…”
Section: Identification Of Fungal Isolatesmentioning
confidence: 99%